Knowledge Extraction In Hopfield Network - Sathasivam, Saratha (2011)
Deduction simplifies the knowledge representation without affecting the knowledge contents. Thus, deduction makes the clauses more compact and easier to be interpreted as a large amount of redundancy may obscure the meaning ofthe represented knowledge.